2020
DOI: 10.3390/agronomy10071044
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modelling of Within-Field Weed Populations; a Review

Abstract: Concerns around herbicide resistance, human risk, and the environmental impacts of current weed control strategies have led to an increasing demand for alternative weed management methods. Many new weed management strategies are under development; however, the poor availability of accurate weed maps, and a lack of confidence in the outcomes of alternative weed management strategies, has hindered their adoption. Developments in field sampling and processing, combined with spatial modelling, can support the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…The cokriged maps exhibited more local detail and less smoothness in their depiction of the variability of weed density. Comparable results were found for other weed species cokriged with UAV-derived variables as covariates [5,13,23]. The improved local detail of the cokriging maps was due to the finer spatial resolution of the UAV-derived secondary variables.…”
Section: Spatial Variability Of Centaurea Dilutamentioning
confidence: 71%
See 3 more Smart Citations
“…The cokriged maps exhibited more local detail and less smoothness in their depiction of the variability of weed density. Comparable results were found for other weed species cokriged with UAV-derived variables as covariates [5,13,23]. The improved local detail of the cokriging maps was due to the finer spatial resolution of the UAV-derived secondary variables.…”
Section: Spatial Variability Of Centaurea Dilutamentioning
confidence: 71%
“…For numerous weed species, it was found that patches occurred more or less at the same location over years indicating that the within-field weed distributions are relatively stable between years. If weeds are expected at the same locations over years, this makes any map produced useful in future years ( [6,13,88,89], among many others). Although, the greater the time between sampling and prediction, the less accurate the prediction becomes [13].…”
Section: Probability Maps For Risk Assessment In Patchy Centaurea Diluta Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Weather monitoring systems are developed to more accurately predict pest occurrence and spread as a result of increasing temperature, frontal patterns, and other atmospheric conditions as well as anthropogenic factors (CAST, 2017). In summary, several quantitative models to determine the spread of plant pests for use in pest risk assessment has been implemented such as for pathogens (Dalal and Singh, 2017), insects (Tonnang et al, 2017;Balikai et al, 2019) and weeds (Hanzlik and Gerowitt, 2016;Somerville et al, 2020).…”
Section: Modelling and Forecasting The Occurrence And Impacts Of Pestsmentioning
confidence: 99%